Optimalisasi keuntungan maksimal UMKM "Alpukat Kocok Sasya" dengan menggunakan metode simpleks (Linear Programming) - Nita Anggriani; Afrilia Lumintang; Angelita Claudia B Adilang; Aprilia Pangemanan Montolalu Jehosua; Fabio Sevcenko Lolowang; Mouren F Pangemanan; Patricia Putri Pinatik (SOSCIED, 2026)
Sasya Avocado Shake UMKM face obstacles in determining the most efficient production combination due to limitations in daily raw materials such as avocados, sweetened condensed milk, liquid milk, glasses, Milo, and cheese. This study aims to formulate a Linear Programming model and determine the optimal solution using the simplex method to obtain maximum profit. A quantitative approach is used through operations research techniques, with data collection in the form of raw material requirements, production costs, selling prices, and production capacity for each variant. The mathematical model was constructed with three decision variables, namely the production of the original variant, cheese, and Milo, accompanied by an objective function to maximize profit and constraints in accordance with the limitations of raw material availability. Manual calculations and the Simplex Calculator application showed that the optimal production combination was to prioritize the original and Milo variants, while the cheese variant was not produced because its profit margin was low and the use of raw materials was more expensive. These findings prove that the simplex method is effective in helping MSMEs allocate resources and encourage production to focus on variants with the highest profits. Linear programming models can be a strategic tool for MSMEs to improve operational efficiency and profits in a sustainable manner.